Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1038/srep08775
|View full text |Cite
|
Sign up to set email alerts
|

Intercalation and Retention of Carbon Dioxide in a Smectite Clay promoted by Interlayer Cations

Abstract: A good material for CO2 capture should possess some specific properties: (i) a large effective surface area with good adsorption capacity, (ii) selectivity for CO2, (iii) regeneration capacity with minimum energy input, allowing reutilization of the material for CO2 adsorption, and (iv) low cost and high environmental friendliness. Smectite clays are layered nanoporous materials that may be good candidates in this context. Here we report experiments which show that gaseous CO2 intercalates into the interlayer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
78
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(93 citation statements)
references
References 60 publications
(77 reference statements)
8
78
2
2
Order By: Relevance
“…There have been extensive studies that demonstrated that solid sorbents with negative charge can display significantly enhanced adsorption of CO 2 [16,28,29]. It is interesting for us to further explore the adsorption of CO 2 on the B 40 fullerene with an extra electron.…”
Section: Adsorption Of Co 2 On B 40 and B 40mentioning
confidence: 98%
“…There have been extensive studies that demonstrated that solid sorbents with negative charge can display significantly enhanced adsorption of CO 2 [16,28,29]. It is interesting for us to further explore the adsorption of CO 2 on the B 40 fullerene with an extra electron.…”
Section: Adsorption Of Co 2 On B 40 and B 40mentioning
confidence: 98%
“…[30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][52][53][54][55][56] With respect to confinement of hydrophobic species, the 2-dimensional interlayer galleries of expandable clays are known to accommodate CO 2 . 6,[18][19][20][21]23,26,38,[57][58][59][60][61][62][63][64] Owing to their natural abundance, environmental friendliness, large internal surface areas, and tunable affinity and specificity for adsorption of small and complex molecules, 37-45,53-56 the expandable clay minerals continue to serve as ideal models for understanding the behavior of hydrophilic and hydrophobic species in …”
mentioning
confidence: 99%
“…1,6,[18][19][20][21][22][23][24][25][26][27][28][29]38,57,58,60,[64][65][66][67] Because of their common natural occurrence, they may also play an important role in geological CO 2 -sequestration reservoirs. 1,6,[18][19][20][21][22][23][24][25][26][27][28][29]38,67,57,58,60,[64][65][66][67] The affinity and specificity of oxide surfaces for intercalates can be controlled by a variety of compositional and structural parameters including substitutions in the tetrahedral and octahedral layers, variability in charge-balancing cations, and coatings of functionalized organic compounds. [38][39][40]...…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Xray diffraction measurements showed negligible expansion for dry clay samples upon exposure to dry CO 2 and that residual water is required to intercalate CO 2 . 1, 21 Exper-4 imental investigations have explored gas sorption on both dry 6,7,[13][14][15]25 and moisture equilibrated 1,7,13,14,17,22,54 clays. In addition, computer simulations have inspected the effect of water on the adsorption of carbon dioxide and methane in clay minerals, and the underlying sorption mechanisms.…”
mentioning
confidence: 99%